2021
DOI: 10.1002/ajp.23326
|View full text |Cite
|
Sign up to set email alerts
|

Western lowland gorillas (Gorilla gorilla gorilla) do not show an aversion to inequity in a token exchange task

Abstract: Although individuals in some species refuse foods they normally accept if their partner receives a more preferred one, this is not true across all species. The cooperation hypothesis proposes that this species‐level variability evolved because inequity aversion is a mechanism to identify situations in which cooperation is not paying off, and that species regularly observed cooperating should be more likely to be averse to inequity. To rule out other potential explanations of inequity aversion, we need to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 62 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Dubreuil et al, 2006; Hopper et al, 2014; Neiworth et al, 2009) and a missing contrast control condition (cfr. Brosnan et al, 2010; Hopper et al, 2014; Sosnowski et al, 2021), we cannot completely differentiate social IA from the social disappointment hypothesis and the reward expectation hypothesis. We did rule out the expectancy violation hypothesis as explanation for the trial refusals in our study by running additional analyses.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Dubreuil et al, 2006; Hopper et al, 2014; Neiworth et al, 2009) and a missing contrast control condition (cfr. Brosnan et al, 2010; Hopper et al, 2014; Sosnowski et al, 2021), we cannot completely differentiate social IA from the social disappointment hypothesis and the reward expectation hypothesis. We did rule out the expectancy violation hypothesis as explanation for the trial refusals in our study by running additional analyses.…”
Section: Discussionmentioning
confidence: 83%
“…While looking at the effect of dominance relations on IA, several studies found that dominant individuals were more sensitive to inequity than subdominants (Bräuer et al, 2006; Brosnan et al, 2010; Dale et al, 2020; Essler et al, 2017; Oberliessen et al, 2016), others have found no such rank effects (Brosnan & de Waal, 2003; Massen et al, 2012; Range et al, 2012; Sosnowski et al, 2021; Van Wolkenten et al, 2007). Again, the socioecology of the species could explain these differing results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PubMed: inequity aversion Duplicates were removed using EndNote 68 , after which the entries were imported into Covidence 69 for screening. Two relevant papers were published after the search was conducted and screened when their authors notified us of their existence 47,53 . The first author undertook the preliminary title and abstract screening; the first and fourth authors both conducted full text review of papers identified as potentially eligible.…”
Section: Web Of Science: All=((fairness or Inequity Or Inequality) An...mentioning
confidence: 99%
“…The importance of this distinction has been acknowledged by much of the literature on IA in nonhuman animals, and most studies investigating IA in animals included conditions designed specifically to rule out the disappointment hypothesis. Typical examples of these are conditions in which the experimenter hands a high quality reward to an empty cage 27,[46][47][48] , and conditions in which the experimenter holds up a high quality reward prior to exchanging but then hands both subject and partner a low quality reward [49][50][51][52][53][54][55] . Some studies successfully demonstrated an effect of social comparison above and beyond disappointment 27,37,52,56,57 , while others did not 37,46,47 .…”
mentioning
confidence: 99%